ADRB3 gene promoter DNA methylation in blood and visceral adipose tissue is associated with metabolic disturbances in men. (February 2014) - Guay, Simon-Pierre; Brisson, Diane; Lamarche, Benoit; Biron, Simon; Lescelleur, Odette; Biertho, Laurent; Marceau, Simon; Vohl, Marie-Claude; Gaudet, Daniel; Bouchard, Luigi
Aim: ADRB3 DNA hypermethylation was recently associated with dyslipidemia in familial hypercholesterolemia (FH). In this study, we verified whether ADRB3 DNA methylation in blood and visceral adipose tissue (VAT) was associated with obesity and its related complications.Methods: DNA methylation levels were measured in the blood of 61 FH men, and the blood and VAT of 30 severely obese men. Common ADRB3 polymorphisms were genotyped in all subjects.Results: Higher ADRB3 DNA methylation levels were significantly associated with lower low-density lipoprotein cholesterol levels (r = -0.40; p = 0.01) in FH, and with a lower waist-to-hip ratio (r = -0.55; p = 0.01) and higher blood pressure (r = 0.43; p = 0.05) in severely obese men. ADRB3 g.-843C>T and p.W64R polymorphisms were found to be strongly associated (p < 0.001) with ADRB3 DNA methylation and mRNA levels.Conclusion: Although further studies are needed, these results suggest that epigenetic changes at the ADRB3 gene locus might be involved in the development of obesity and its related metabolic complications.